Magnesium biofortification of Italian ryegrass (Lolium multiflorum L.) via agronomy and breeding as a potential way to reduce grass tetany in grazing ruminants - Diriba B. Kumssa; J. Alan Lovatt; Neil S. Graham; Sarah Palmer; Rory Hayden; Lolita Wilson; Scott D. Young; R. Murray Lark; Beth Penrose; E. Louise Ander; Russell Thompson; Lin-Xi Jiang; et al. (Plant and Soil, 2020)
Aim Magnesium (Mg) deficiency (known as grass tetany) is a serious metabolic disorder that affects grazing ruminants. We tested whether Mg-fertiliser can increase Mg concentration of Italian ryegrasses ( Lolium multiflorum L.) including a cultivar (cv. Bb2067; ‘Magnet’), bred to accumulate larger concentrations of Mg. Methods Under controlled environment (CE) conditions, three cultivars (cv. Bb2067, cv. Bb2068, cv. RvP) were grown in low-nutrient compost at six fertiliser rates (0–1500 μM MgCl 2 .6H 2 O). Under field conditions, the three cultivars in the CE condition and cv. Alamo were grown at two sites, and four rates of MgSO 4 fertiliser application rates (0–200 kg ha −1 MgO). Multiple grass cuts were taken over two-years. Results Grass Mg concentration increased with increasing Mg-fertiliser application rates in all cultivars and conditions. Under field conditions, cv. Bb2067 had 11–73% greater grass Mg concentration and smaller forage tetany index (FTI) than other cultivars across the Mg-fertiliser application rates, sites and cuts. Grass dry matter (DM) yield of cv. Bb2067 was significantly ( p < 0.05) smaller than cv. Alamo. The effect of Mg-fertiliser rate on DM yield was not significant ( p ≥ 0.05). Conclusions Biofortification of grass with Mg through breeding and agronomy can improve the forage Mg concentration for grazing ruminants, even in high-growth spring grass conditions when hypomagnesaemia is most prevalent. Response to agronomic biofortification varied with cultivar, Mg-fertiliser rate, site and weather. The cost:benefit of these approaches and farmer acceptability, and the impact on cattle and sheep grazing on grasses biofortified with Mg requires further investigation.